On Nano Ɽ-Space Application - Esmaeel, R. B. (Iraqi Journal of Science, 2024)
This study introduces a novel topological space named the nano Ɽ-space, which is based on the principles of nano topological spaces. Thus, the reconstruction of this space and their properties are demonstrated and explored, accompanied by illustrative examples to aid in understanding its nature. Furthermore, the investigation of the practical implications of the nano Ɽ-space through a series of case studies involving pediatric patients diagnosed with leukemia. Then, by examining the symptoms exhibited by these patients and their impact on the equivalence relations within the nano Ɽ-space, the elucidate the applied aspect of this novel topological framework. the findings indicate that the presence of unexplained bruises on the body emerges as a fundamental and indispensable symptom, allowing us to definitively diagnose the presence of leukemia in a patient.